2009
DOI: 10.1097/prs.0b013e31819e26d5
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Concern Regarding Computed Tomography Irradiation in Craniofacial Surgery

Abstract: The safety of medical radiation, particularly computed tomography, has recently received much attention in both the medical literature and the popular press. As knowledge regarding side effects of radiation exposure has increased, so have attempts to limit doses to patients through more selective use of scans and transitions to lower-dose protocols to conform to the As Low As Reasonably Achievable (ALARA) principle. This trend has been apparent across many fields within medicine, including craniofacial surgery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 29 publications
0
21
0
2
Order By: Relevance
“…Too often the discussion focused on the quality of images rather than on radiation protection. It is beyond question that a thin-layer CT scan optimally depicts cranial sutures [10]. But this is of little importance in clinical practice as our results demonstrate (Fig.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Too often the discussion focused on the quality of images rather than on radiation protection. It is beyond question that a thin-layer CT scan optimally depicts cranial sutures [10]. But this is of little importance in clinical practice as our results demonstrate (Fig.…”
Section: Discussionmentioning
confidence: 56%
“…3). Remarkably enough, Domeshek et al [10] recently demonstrated that the existing low dose protocols might even be further ) and plain Xray with a left-sided anterior plagiocephaly (c, d) due to premature closure of the coronal suture. Note the typical characteristics of the lesser sphenoid wing on the affected side.…”
Section: Discussionmentioning
confidence: 96%
“…Over the last 5 years, there have been emerging international concerns regarding ionizing radiation and its potential for tumor induction and developmental delays. 25,26 Third, morphometric evaluation in this study was limited to 12 months following extended strip craniectomy, which precluded long-term assessment of surgical correction. Serial CT scans for the purpose of short-and long-term morphometric appraisal, however, would not have been medically ethical in the context of radiation safety.…”
Section: Seruya Et Almentioning
confidence: 99%
“…Some author's have presented calculations of estimations of increased cancer incidence due to radiation from CT investigations [15]. However, with modern CT equipment the dose from a CT of the head, in a child, is equal to that of the background radiation during 1-2 months and, thus, adds very little risk [16].…”
Section: Discussionmentioning
confidence: 99%